Governança metropolitana e sustentabilidade: uma análise da gestão dos resíduos sólidos em Natal e Parnamirim - Albuquerque, Pedro Augusto Filgueira (2015)
Nowadays the rapid growth of urban centers, the accumulation of social and environmental demands, the relationship between public policy and increasingly complex problems accentuates the feeling that cities undergo an urban crisis. This crisis is especially characterized by its multidimensionality, which goes through economic, cultural, ethical, environmental and, above all, political issues. In order to study the core of this crisis that is manifested by the urbanization process and has in its exacerbation on the metropolitan areas was conducted conceptual and theoretical study of the meaning of sustainable development applied to the everyday reality of cities, extracting from this debate concepts, such as: sustainable territorial development, administrative sustainability and political sustainability. Looking forward to test this the practical applicability of these theoretical concepts studied, an empirical study was done on the reality of metropolitan solid waste in Natal, Rio Grande do Norte, Brasil. According to the recent theoretical debate, the waste comprises a sector of the urban environmental crisis that best represents the relationship between man and environment. Ensuring the multidimensionality of environmental issues through the “Saber Ambietal” (LEFF, 2005), was made a extensive qualitative study correlating the concepts of sustainable territorial development, metropolitan governance and “Saber Ambiental” applied on solid waste. The results point to the real challenges of municipal government in understanding the real situation, take action and change the inertia in which have operated in recent decades. The results also showed the importance of transforming environmental issues in political, in other words, struggle for ideas, ideological and ethical references.